2019
DOI: 10.1002/slct.201901465
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Ternary Nickel–Iron oxide as Bifunctional Catalyst for Electrochemical Water Splitting

Abstract: The development of noble metal free, robust catalyst is highly sought for commercialization of clean, renewable energy technology and to replace the fossil fuel‐based energy equipments. Herein, we report a highly efficient and stable ternary Nickel Iron oxide (NiFe2O4) electrocatalyst for bifunctional oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline medium. The as‐synthesized NiFe2O4 has been confirmed by techniques like FESEM, HR‐TEM, powder X‐ray diffraction (XRD), and X‐ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 63 publications
2
49
0
Order By: Relevance
“…Phase‐purity was also checked by Raman spectroscopy, especially to exclude the presence of hematite by‐phases, since small amounts of hematite in spinel nanocrystals might not be detected by PXRD. For cubic spinels with F d true3 m space group, five Raman active lattice modes were expected: A 1g (691 cm −1 )+ E g (332 cm −1 )+3 T 2g (201 cm −1 , 487 cm −1 , 570 cm −1 ) [54–57] . The A 1g signal corresponds to the symmetric stretching mode of M−O bonds in tetrahedral units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase‐purity was also checked by Raman spectroscopy, especially to exclude the presence of hematite by‐phases, since small amounts of hematite in spinel nanocrystals might not be detected by PXRD. For cubic spinels with F d true3 m space group, five Raman active lattice modes were expected: A 1g (691 cm −1 )+ E g (332 cm −1 )+3 T 2g (201 cm −1 , 487 cm −1 , 570 cm −1 ) [54–57] . The A 1g signal corresponds to the symmetric stretching mode of M−O bonds in tetrahedral units.…”
Section: Resultsmentioning
confidence: 99%
“…For cubic spinels with Fd � 3m space group, five Raman active lattice modes were expected: A 1g (691 cm À 1 ) + E g (332 cm À 1 ) + 3 T 2g (201 cm À 1 , 487 cm À 1 , 570 cm À 1 ). [54][55][56][57] The A 1g signal corresponds to the symmetric stretching mode of MÀ O bonds in tetrahedral units. The T 2g (2) and T 2g (3) signals can be assigned to the asymmetric stretching mode and to the asymmetric bending of MÀ O bonds in octahedral units, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Moreover, NiFe 2 O 4 was investigated as a bifunctional electrocatalyst for OER and hydrogen evolution reaction (HER) in alkaline medium. [12] In addition to oxides, iron nickel layered double hydroxides (FeNiO x H y ) have been identified as highly active electrocatalysts for the OER. [13] Unfortunately, nanoparticles have several disadvantages, one of which is that they must be immobilized and electrically connected to the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Liu et al reported on the hydrothermal growth of spinel NiFe 2 O 4 in the form of nanospindle arrays on FeNi 3 foam, which were successfully applied as electrodes for the OER [11] . Moreover, NiFe 2 O 4 was investigated as a bifunctional electrocatalyst for OER and hydrogen evolution reaction (HER) in alkaline medium [12] . In addition to oxides, iron nickel layered double hydroxides (FeNiO x H y ) have been identified as highly active electrocatalysts for the OER [13] …”
Section: Introductionmentioning
confidence: 99%